PENGUJIAN VIGOR BENIH JAGUNG MELALUI DAYA BERKECAMBAH, BOCORAN KALIUM DAN DAYA HANTAR LISTRIK AIR RENDAMAN BENIH: Vigor Testing of Corn Seeds through Germination, Potassium Leakage, and Electrical Conductivity of Seed Soaking Water - Mariani Mariani (Jurnal Agrotan, 2018)
Vigor corn seeds affect the growth and production of corn plants. This study aims to determine the level of decrease in corn seed vigor for a storage period of 12 months and 24 months for the Bisma, Lamuru and Gumarang varieties. This study was conducted in the Cereal Crops Research Institute in Maros, South Sulawesi. The vigor test method was carried out in two ways, namely: (1) direct vigor test method by observing germination (2) indirect vigor test method by measuring the electrical conductivity of seed soaking water and potassium leakage. Three corn varieties were used as research materials, namely: Bisma, Lamuru and Gumarang with a storage period of 12 months and 24 months. The results showed that all varieties observed were decreased of their vigor seed levels from a storage period of 12 months and 24 months. It can be seen from the decrease in germination and increase in the value of electrical conductivity of seed soaking water and potassium leakage.